Paired plot experiments to assess impact of invasive species on native floral diversity in Pakistan - Qureshi, Huma; Anwar, Tauseef; Mohibullah, Muhammad; Fatima, Sammer; Younas, Rafia; Habiba, Ume; Malik, Laraib; Hanif, Asma; Iqbal, Muhammad (Frontiers in Environmental Science, 2023)
The threat of invasion is growing globally and endangers biodiversity. Exotic invasive plants are putting a harm to the vegetation of Pakistan's Pothwar region, which is a biodiversity hotspot. In the current study, the effects of Broussonetia papyrifera, Parthenium hysterophorus, Xanthium strumarium and Lantana camara on the local flora in the Pothwar area were examined. Two categorical groups (invaded and non-invaded) were used in a dichotomized experimental design to collect data. Using the software PRIMER-7 and IBM SPSS v. 21, different diversity indices including Margalef's index of species richness, Shannon index of diversity, and Simpson index of dominance were measured and compared between invaded and control plots. In comparison to the experimental plots, the control plots had an average of more individuals and diversity. On a multivariate scale, non-metric multidimensional scaling (nMDS) and analysis of similarity (ANOSIM) revealed higher species richness in control plots. The invasion effect of L. camara was the highest, followed by X. strumarium, P. hysterophorus, and B. papyrifera.